Broadband in Russia - Rossotto, Carlo Maria (World Bank, Washington, DC, 2015)
It is widely recognized that broadband is of fundamental importance to the social and economic development of a nation. The focus of the paper is on infrastructure-related actions; measures to stimulate demand for broadband are, therefore, only marginally addressed. This paper aims to provide a platform for debate with the Russian counterparts in the sector, and to discuss the measures needed to develop broadband in support of actions aimed at economic growth. This paper examines the broadband market in Russia and preconditions for its sustainable development. It begins by presenting arguments demonstrating the importance of broadband to the overall economic development of Russia, including from the perspective of diversification of the economy and new job creation. The paper benchmarks Russia s broadband performance with Organization of Economic Cooperation and Development (OECD) comparators, as well as with other nations leading the way in broadband diffusion. The paper takes stock of the existing broadband market structure in Russia and its main players as they stand today, including the regulatory and legal environment of the market for both fixed and mobile broadband. Finally, the paper provides a set of recommendations that addresses the issue of sustainability in Russian broadband delivery, and how it can continue its acceleration in the years to come.